2023
DOI: 10.1002/brb3.2884
|View full text |Cite
|
Sign up to set email alerts
|

Higher prevalence of idiopathic normal pressure hydrocephalus‐like MRI features in progressive supranuclear palsy: An imaging reminder of atypical parkinsonism

Abstract: Objectives:The classic triad of idiopathic normal pressure hydrocephalus (NPH) encompass gait disturbance, cognitive impairment, and urinary incontinence. These symptoms overlap with parkinsonism but with distinct treatment. Lacking applicable differentiation also hampers the prediction to therapeutic response. Here, we try to clarify this issue among different Parkinsonian syndromes and propose some innovative thinking while approaching a patient with parkinsonism and hydrocephalus concomitantly.Methods: Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…After duplicate record elimination, 1096 records were screened by reviewing the title and abstract, eliminating 702 further studies. For the 337 remaining records, full texts were reviewed, eliminating 315 records (unrelated content: n = 280; patient or control group consisting of <10 subjects: n = 22 [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]; full text unavailable: n = 1 [38]; non-extractable data: n = 1 [39]; data in median/quartiles: n = 4 [40][41][42][43]; identical study cohorts or study cohorts with significant overlap: n = 2 [8,44]; data on PSP/MSA cohorts without distinction of RS/MSA-P phenotypes: n = 5 [45][46][47][48][49]). Five studies were identified via manual search of related papers, references, and citing papers [13,[50][51][52][53].…”
Section: Literature Search and Screening Resultsmentioning
confidence: 99%
“…After duplicate record elimination, 1096 records were screened by reviewing the title and abstract, eliminating 702 further studies. For the 337 remaining records, full texts were reviewed, eliminating 315 records (unrelated content: n = 280; patient or control group consisting of <10 subjects: n = 22 [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]; full text unavailable: n = 1 [38]; non-extractable data: n = 1 [39]; data in median/quartiles: n = 4 [40][41][42][43]; identical study cohorts or study cohorts with significant overlap: n = 2 [8,44]; data on PSP/MSA cohorts without distinction of RS/MSA-P phenotypes: n = 5 [45][46][47][48][49]). Five studies were identified via manual search of related papers, references, and citing papers [13,[50][51][52][53].…”
Section: Literature Search and Screening Resultsmentioning
confidence: 99%
“…The triad of symptoms for idiopathic normal pressure hydrocephalus (iNPH) includes 1) urinary incontinence, 2) gait disturbances, and 3) cognitive impairment along with ventriculomegaly (21). There is evidence suggesting similarities between progressive supranuclear palsy (PSP) and normal pressure hydrocephalus (NPH) (21).…”
Section: Parkinsonism In the Course Of Normal Pressure Hydrocephalusmentioning
confidence: 99%
“…Also, overlapping imaging findings across different disorders can create diagnostic challenges. [ 5 6 ] Studying the overlapping MRI markers among different disorders has the potential to identify markers that could enhance diagnostic accuracy and provide insight into underlying commonalities in pathophysiology.…”
mentioning
confidence: 99%